Teachers’ perspective on the use of artificial intelligence on remote experimentation - Lizano-Sánchez, Fiorella; Idoyaga, Ignacio; Orduña, Pablo; Rodríguez-Gil, Luis; Arguedas-Matarrita, Carlos (Frontiers in Education, 2025)
Remote Laboratories have become crucial educational resources due to their implementation in institutions that have adopted hybrid teaching models. Moreover, artificial intelligence (AI) has increasingly been used to develop educational support tools. Remote Laboratories suffer from a limitation: when students conduct experimental activities, instructors cannot always be immediately available to resolve doubts. To address this limitation, a virtual assistant was integrated into the Acid–Base Titration II Remote Laboratory. The aim of this research is to understand the perspective of chemistry teachers from the Common Basic Cycle of the University of Buenos Aires on the use of this artificial intelligence tool. For this purpose, a focus group was conducted in which a series of questions were asked before and after using the AI tool. The findings reveal that teachers perceive great potential in the combination of these technologies. Furthermore, the virtual assistant could offer personalised assistance in real time, which ensures accompaniment during the completion of the Remote Laboratory.